Assessment of Cow Dung on Nutrient Uptake, Soil Physicochemical Properties, Growth and Yield of Okra in Jalingo, Taraba State, Nigeria - Onwu, Clement Alex; Emmanuel, Danladi; Amadu, Lanki Dairus (Darul Yasin Al Sys, 2026)
Declining soil fertility remains a major constraint to sustainable agricultural production in the Guinea Savannah zone of Nigeria, necessitating the evaluation of organic amendments that can improve soil quality and crop productivity. This study evaluated the effects of cow dung application on nutrient uptake, soil physicochemical properties, growth, and yield of okra in Jalingo, Taraba State, Nigeria. A field experiment was conducted during the 2022 cropping season using a randomized complete block design with three replications. Five treatments were applied: control at 0 t ha⁻¹ and cow dung at 15, 20, 25, and 30 t ha⁻¹. Okra leaves were sampled for nutrient uptake at 50% flowering, while soil samples were collected at a depth of 0–30 cm before planting and after harvest for the analysis of particle size distribution, pH, organic carbon, total nitrogen, available phosphorus, exchangeable bases, and cation exchange capacity. The findings showed that cow dung significantly enhanced nutrient uptake, with the 30 t ha⁻¹ treatment recording the highest values for nitrogen, phosphorus, and potassium uptake. Soil analysis further indicated that higher cow dung rates, particularly 25–30 t ha⁻¹, significantly improved soil pH, organic carbon, available phosphorus, exchangeable bases, and cation exchange capacity compared with the control treatment. Significant differences were also observed in plant height, pod length, pod width, and pod weight across cow dung application rates. The highest pod yield of 8.65 t ha⁻¹ was recorded under the 30 t ha⁻¹ treatment, which was statistically similar to the 25 t ha⁻¹ treatment, with 8.28 t ha⁻¹. The study concludes that cow dung application at 25–30 t ha⁻¹ is more effective in improving soil fertility, nutrient uptake, okra growth, and yield under the conditions of the study area. These findings contribute to sustainable soil fertility management by supporting the use of cow dung as an organic amendment for enhancing okra production in the Guinea Savannah zone of Nigeria.